Flexible Na batteries. Issue 1 (11th August 2019) - Zhao, Chenglong; Lu, Yaxiang; Chen, Liquan; Hu, Yong‐Sheng
Abstract: Flexible energy storage devices have gained significant attention because of the increasing needs of bendable displays, wearable electronics, and flexible displays. Flexible Na‐based rechargeable batteries are the promising power sources in such products due to their low cost and wide availability. In this review, we firstly introduce the structural superiority of flexible Na‐based batteries and summarize their main components including cathodes, electrolytes, and anodes. Moreover, fabrication of their flexible components is discussed in detail, with specific emphasis on material selection, particularly for solid‐state electrolytes. This is followed by an overview highlighting recent progress in the development of prototypes of flexible Na‐ion batteries and beyond. Finally, perspectives on future challenges for the development of flexible Na batteries are proposed. Abstract : Flexible energy storage devices are the promising power sources for bendable displays, wearable electronics, and flexible devices. This review discusses the structural superiority of flexible Na‐based batteries and their main components, including cathodes, electrolytes, and anodes. Further perspectives on the development of flexible Na‐ion batteries and beyond are proposed.